If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = -3x + -12 Reorder the terms: 12 + 3x = -3x + -12 Reorder the terms: 12 + 3x = -12 + -3x Solving 12 + 3x = -12 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 12 + 3x + 3x = -12 + -3x + 3x Combine like terms: 3x + 3x = 6x 12 + 6x = -12 + -3x + 3x Combine like terms: -3x + 3x = 0 12 + 6x = -12 + 0 12 + 6x = -12 Add '-12' to each side of the equation. 12 + -12 + 6x = -12 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = -12 + -12 6x = -12 + -12 Combine like terms: -12 + -12 = -24 6x = -24 Divide each side by '6'. x = -4 Simplifying x = -4
| 25x^2-80x+64= | | 7y=5y+14 | | -1+21=b+18 | | 14p-16p+9-4= | | 8x+5=6x+31 | | 2x+8=-3x-12 | | 7x+y+4=-16+10y-x | | y+9x=-6 | | (y^2-7)(4y^2-2y+2)= | | -2(y+12)=7-9 | | 2m^2-14m+24= | | 2x-7(7x+8)=3x-40 | | -42-n=-120 | | 3x+12+x= | | 2x+9-x=8+2x-6 | | F(t)=sin(2t) | | 2(3+5x)-4=62 | | -7(9a-4)=31 | | 17s=18s-3 | | 4y+5=3y-4 | | 6x+12y=8 | | 2x-g=7 | | 0.25(84-32n)-n= | | g+4=2g-6 | | 9+12+16= | | 3g-11(-1)=14 | | -3-2x=-3 | | g=2(-1)+3 | | 07(h+2)+1.6=17 | | 3x^2(x-3)=0 | | 57-(5x+15)=5(x+4)+x | | y=2(3y-5)-8 |